Cerebral Hyperperfusion Syndrome after Carotid Revascularization: A Brief Review - Anand, Saurabh; Sahoo, Asish K. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Cerebral hyperperfusion (CHS) syndrome is a relatively rare but potentially devastating event that can complicate carotid endarterectomy and carotid stenting. It is associated with increased cerebral perfusion usually more than 100% from the baseline along with ipsilateral headache, seizures, focal neurological deficits, encephalopathy, intracranial hemorrhage, or subarachnoid hemorrhage. Various risk factors have been identified but most important risk factor is preprocedure evidence of reduced cerebral vasoreactivity with or without contralateral severe carotid stenosis or occlusion. Although diagnosis is suspected in patients with clinical suspicion, it can be radiologically demonstrated with computed tomography (CT), magnetic resonance imaging (MRI), and by dynamic imaging of cerebral perfusion such as transcranial Doppler (TCD), CT, and MR perfusion, and single-photon emission computed tomography (SPECT). Management is usually centered around prompt recognition and active regulation of blood pressure in perioperative and postoperative periods to limit the rise of cerebral blood flow. Prognosis depends on the early detection and prompt management of CHS. If detected early, coupled with intensive blood pressure management, almost all patients will recover over a period of time. For those patients who are diagnosed late and those progressing to intracranial hemorrhage (ICH), the prognosis is not nearly as good.
Keywords: carotid artery stenting; carotid endarterectomy; cerebral hyperperfusion; transcranial Doppler